Rethinking ghosts in world religions - Pu, Muzhou. (Numen Book Series, 2009)
The central theme of this volume is to re-examine the received concepts and images of ghosts in various religious cultures ranging from the Ancient Near East and Egypt to the Old Testament, the Classical Era, Early Medieval and Early Modern Europe, Early India, and Medieval China. As a religious phenomenon, the realm of ghosts has been less studied than the realm of the divine. Through a collaborative effort by scholars from different disciplines, this volume proposes a multi-cultural approach to construct a wider and complicated picture of the phenomenon of ghosts and spirits in human societies and to have a grasp of the various problems involved in understanding the phenomenon of ghost.